Population genetic analysis of Arapaima gigas, one of the largest freshwater fishes of the Amazon basin: Implications for its conservation - Hrbek, Tomas; Farias, Izeni P.; Crossa, Marcelo; Sampaio, Iracilda C.; Porto, Jorge Ivan Rebelo; Meyer, Axel (Animal Conservation, 2005)
The present study reports the first population genetic analysis of Arapaima gigas, an important but critically over-exploited fish species of the Amazon basin. We sequenced two discontinuous mitochondrial DNA regions of 1204 base-pairs (bp) (NADH1 segment) and 1143bp (ATPase segment) from 139 individuals of A. gigas representing eight localities spanning the Amazon basin from Iquitos, Peru to Macapá, Brazil. We discovered 34 haplotypes separated by 44 segregating sites. The two most common haplotypes are shared among all populations and isolation-by-distance appears to be the most important population dynamic, although there is no significant association between geographical distance and genetic differentiation. Observed patterns of differentiation appear to be attributable largely to anthropogenic factors associated with over-exploitation. Greatest haplotypic diversity exists upstream of Manaus and in areas away from large centres of population. The female variance and inbreeding effective population sizes are approximately 150 000 individuals and localities in the Amazon basin are connected by gene flow. Naturally low levels of population differentiation and relatively high between-population connectivity is encouraging for the conservation and management of A. gigas. If strategically placed biological reserves were created throughout the Amazon basin to act as sources of emigrants within a source-sink metapopulation model, we believe locally depleted populations can be re-populated and maintained by individuals immigrating from these reserves. © 2005 The Zoological Society of London.
Keywords: Conservation Genetics; Conservation Management; Fish; Genetics, Population; Arapaima Gigas; Pisces